Effectiveness of experiment-based learning method in improving elementary school students' understanding of Islamic physics concepts - Adinda Azzahra; Abhanda Amra; Rizki Pebrina; Adam Mudinillah (Yayasan Adra Karima Hubbi, 2024)
This research is driven by the importance of developing effective learning methods to improve the understanding of Islamic physics concepts in elementary school students. The experiment-based learning method was chosen because it provides opportunities for students to learn actively through direct experience, observation, and reflection. Research that specifically evaluates this method in terms of students' understanding of Islamic physics in primary schools is limited. The purpose of this study is to fill the gap on the understanding of Islamic physics concepts in elementary school students by determining whether the experiment-based learning method is effective in this regard. This research method is using quantitative method, which collects data through distributing questionnaires using google from to educators. Quantitative methods are data that contain numbers. Then the questionnaire results are processed using SPSS, which is presented in the form of graphs or tables. This method is used to obtain clearer and complex results that can strengthen the data to be carried out and interviews provide written text of educators. The results showed that there was a significant increase in understanding of physics concepts between students who were taught. The experimental approach provides direct experience to students, allowing them to see and feel the principles of physics in a real context and relevant to Islamic values.